Research trends of nature-based solutions: from urban to climate change - Yang, Hyunyoung; Chae, Jeongyeon; Song, Cholho; Choi, Eunho (Frontiers in Forests and Global Change, 2024)
As one of the efforts to combat climate change and the biodiversity crisis, an interest in nature-based solutions (NbS) has been growing. Although there have been diverse discussions on NbS, it is still insufficient to find a quantitative evaluation of the global research trends in which field and to what extent NbS has been studied. In this regard, this study employed Latent Dirichlet Allocation (LDA) topic modeling and keyword analysis to quantitatively evaluate the research trends of NbS. Among research papers on NbS searched on SCOPUS, 2625 studies (2009-2022) were analyzed by LDA. As a result, NbS-related articles were classified into seven topics (i.e., Urban governance, Urban green infrastructure, Wastewater treatment, Coastal protection, Flood mitigation, Carbon sequestration, and Sustainable agriculture). Of these, the urban and water-related topics accounted for the largest proportion. In contrast, the carbon sequestration and sustainable agriculture topics accounted for a smaller proportion, but the proportion significantly increased over time. As a result of keyword analysis, the frequency of urban and water keywords remained high. In contrast, the frequency of climate change and carbon keywords was low and has recently increased. In the keyword network, the co-occurrence frequency and connection of urban and water keywords were initially high. Still, over time, keywords related to climate change and carbon increased similarly to those related to urban and water. The findings of this study imply that NbS has mainly focused on urban and waterrelated researches. Still, climate change and carbon-related researches may also be actively handled in relation to NbS in the near future. Keyword(s) whose betweenness centrality ranking(s) (1) remain on the top over time are marked by yellow; and (2) increase over time are marked by orange.